Long-Term Performance of Ten North American Pawpaw Cultivars in Missouri, USA - Bezalel Adainoo; Patrick Byers; Kiruba Krishnaswamy; David Redhage; Kenneth Hunt; John D. Avery; Caleb S. O’Neal; Andrew L. Thomas (International Journal of Fruit Science)
North American pawpaw (Asimina triloba) is an undeveloped tree fruit crop indigenous to the eastern United States. Recent breeding efforts have set the stage for successful cultivation of pawpaw, but cultivar evaluations among geographically distinct environments are needed to advance this unique specialty crop. A significant genotype by environment experiment incorporating 10 pawpaw cultivars, 350 trees, and four sites across Missouri and Oklahoma (USA) was established in 2002–03. Data across 19 years of cultivar performance, tree growth, and fruit production at the three Missouri sites were evaluated. The cultivar “PA Golden” produced the largest trees, whereas “Overleese” struggled with long-term survival, tree growth, and fruit production. “PA Golden” also tended to produce earlier crops, whereas “Sunflower” produced very high yields later into the growing seasons compared with other cultivars. “Susquehanna” consistently produced the largest fruits, averaging 184 g across the three sites and multiple years. Pawpaw trees were very productive in the Missouri environment over 19 years and show excellent promise as an economically viable specialty crop.